Hypersensitivity pneumonitis: Antigen diversity and disease implications - Nogueira, R (2019)
Hypersensitivity pneumonitis (HP) is an immune-mediated syndrome triggered by inhalation of a wide variety of allergens, to which an individual has previously been sensitized. More than 200 agents responsible for the disease have already been identified; however, HP occurs only in a small number of individuals exposed to causal antigens. The present report provides an overview of the role of antigen role in HP, highlighting its diversity, research methods, and prevention strategies, as well as the impact on disease prognosis following elimination of antigen. HP is an underdiagnosed disease and, therefore, it is difficult to accurately estimate its incidence. Triggering antigens can be divided into six broad categories: bacteria, fungi, mycobacteria, animal and plant proteins, chemicals, and metals, represented by disease prototypes. The identification of causal antigen is a major challenge; it is impossible to obtain in about 30–60% of cases. The acute form of HP, with early detection and immediate eviction of causal antigen, tends to have an excellent prognosis. In the chronic form, partial recovery of disease is still possible; however, some cases tend to progress to fibrosis, even after removal from exposure. In conclusion, HP diagnosis should be based on a proactive search for potential antigen sources, although their identification is hampered by the lack of standardized methods of demonstrating the specific antigen sensitization. Antigen avoidance is a critical determinant in disease prognosis.